2015
DOI: 10.31186/jagrisep.12.2.133-146
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Daya Saing Usahatani Kelapa Sawit Di Kabupaten Mukomuko (Studi Kasus Desa Bumi Mulya)

Abstract: This study aimed to analyze the competitiveness of palm oil farming (competitive and comparative advantage)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…SRP value more than zero shows that generally government policy has cause oil palm farming smaller production costs than its opportunity cost. This result supported by (Aprizal et al, 2015) who said that generally, government policy such as market distortion can give a positive impact on the producer. In this case, oil palm farmers on production pay lower than the opportunity cost.…”
Section: Government Policy Impact On Input -Outputmentioning
confidence: 66%
See 1 more Smart Citation
“…SRP value more than zero shows that generally government policy has cause oil palm farming smaller production costs than its opportunity cost. This result supported by (Aprizal et al, 2015) who said that generally, government policy such as market distortion can give a positive impact on the producer. In this case, oil palm farmers on production pay lower than the opportunity cost.…”
Section: Government Policy Impact On Input -Outputmentioning
confidence: 66%
“…This fluctuation can happen both on input price nor output price. The sensitivity research on oil palm farming at Bumi Mulya Village Muko-muko Residence showed that the increasing and the decreasing of input-output price were very sensitive to oil palm farming (Aprizal et al, 2015). According to (Asrtrini, 2013) It's interesting to analyze the competitiveness of this oil palm farming, describe its sensitivity on input-output changing, and analyze the impact of government policy on input-output when facing fluctuation price on oil palm farming at suboptimal land.…”
Section: Introductionmentioning
confidence: 99%
“…Hal ini membuka wawasan petani yang berdomisili di sekitar perkebunan tersebut untuk menanam kelapa sawit, bahkan banyak petani yang mengkonversi komoditas menjadi kelapa sawit. Pendapatan petani yang sebagian besar atau 90,69% berasal dari kelapa sawit, menyebabkan petani menaruh harapan besar terhadap usahatani yang mereka kelola (Aprizal, Asriani, & Sriyoto, 2013).…”
Section: Intisariunclassified
“…The commodity competitiveness can be measured with the comparative advantage indicators, such as the labor and land productivity. According to the Asian Development Bank (1992 in Aprizal, 2013), the comparative advantage is the ability of a region to produce with a relatively low cost. Comparative advantage can also be measured with the social value of cost of production by using the shadow price of input and output.…”
Section: Introductionmentioning
confidence: 99%